(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The civil engineering structures with floating column are a regular element in the cutting edge multistory construction. Such elements are profoundly undesirable in building implicit seismically dynamic ranges. This study highlights the significance of expressly perceiving the vicinity of the structures with and without floating columns. Seismic analysis is carried out on G+7 story building with different alternative location for floating column considering the presence and absence of infill effect. Different structural configurations such as Floating column resting on beam which is supported on column, and Providing RCC wall between columns which is supported by frame having floating column are analysed using professional software Etabs-2013. The response of structure is studied in form of Base-Shear, Storey Shear and Storey Displacement, Member forces of Buildings with and without Floating Columns for seismic zone IV subjected to medium soil profile by seismic coefficient method and response spectrum method referring to IS 1893-2002.